2004
DOI: 10.1111/j.1574-6968.2004.tb09737.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a promoter motif regulating the major DNA damage response mechanism ofMycobacterium tuberculosis

Abstract: The principal response of many bacteria to DNA damage is mediated by a mechanism dependent on the LexA and RecA proteins. However, Mycobacterium tuberculosis was recently reported to regulate a majority of DNA repair genes independently of RecA and LexA, suggesting that an unknown RecA/LexA-independent mechanism controls the major DNA damage response pathway in this organism. Here we have identified a motif tTGTCRgtg-8nt-TAnnnT that defines a novel RecA/LexA-independent promoter (RecA-NDp) of M. tuberculosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 31 publications
2
46
0
Order By: Relevance
“…Analysis of LexA binding in vivo revealed that the mycobacterial SOS box is specified by the consensus sequence TCGAACnnnnGTTCGA . However, many of the DNA repair genes of M. tuberculosis have been shown to be DNA-damage-inducible in a LexA/RecAindependent manner, revealing the existence of an overlapping stress response system in mycobacteria (Gamulin et al, 2004;Rand et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of LexA binding in vivo revealed that the mycobacterial SOS box is specified by the consensus sequence TCGAACnnnnGTTCGA . However, many of the DNA repair genes of M. tuberculosis have been shown to be DNA-damage-inducible in a LexA/RecAindependent manner, revealing the existence of an overlapping stress response system in mycobacteria (Gamulin et al, 2004;Rand et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The basis for the downregulation of the RecA-NDp and ESX-1 genes is unknown, but we speculate that these genes are regulated by an alternative sigma factor that is at a competitive disadvantage in the presence of increased levels of SigA, or has reduced expression in TB294-pSigA. Promoters for both sigG and sigH contain the RecA-NDp motif (Gamulin et al, 2004), and additional evidence links sigG to the DNA-damage response (Lee et al, 2008). However, sigH actually showed a slight increase in expression (1.5-fold) in TB294-pSigA (data not shown), and sigG (Rv0182c) expression was below detectable levels in our array analysis, although its neighbouring genes (Rv0181c, Rv0184 and Rv0185) did have lower expression levels in TB294-pSigA (Supplementary Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…These genes include the DNA repair genes recA, recX, radA, ogt and alkA. The RecA nondependent promoter (RecA-NDp) motif was identified upstream of genes that are activated in response to DNA damage, independently of RecA and LexA (Gamulin et al, 2004). Most DNA repair genes in M. tuberculosis that are induced by DNA damage are regulated independently of RecA (Rand et al, 2003), and promoter sequences containing the RecA-NDp motif have been shown to be required for the RecA-independent induction of recA itself and Rv2719c (Brooks et al, 2006;Davis et al, 2002;Gopaul et al, 2003), both of which are expressed at lower levels in TB294-pSigA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations